Glocalisation, foreign direct investment and regional development perspectives: Empirical results for West German regions - Hermann Knödler; Ulrich Albertshauser (Hamburg Institute of International Economics (HWWA), 2001)
The present paper examines the economic development perspectives of the manufacturing sector of 31 major West German regions in the process of globalisation. Public statistics do not provide FDI data on a regional basis. Therefore our study was based on indicators based on the data from the INDAT-file which gives information about some 6,500 West German manufacturing firms in 1986, 1990 and 1996. The paper draws a stylised picture of the regional structure of West German FDI involvement in the manufacturing sector. The present participation in glocalisation benefits and the mid term development perspectives showed that Hamburg, Darmstadt and Oberbayern belong to the winners of glocalisation. In order to evaluate the long term development perspectives of the industrial cores we checked which regions had far above average access to the future growing areas of the world through FDI outflows. It turned out, that Oberbayern, Stuttgart and Hamburg face the best long term perspectives. Between 1986 and 1996 disparities between the investigated regions with regard to their integration in the global division of labour through FDI-flows have decreased, especially between peripheral regions. – – Die vorliegende Studie untersucht die ökonomischen Entwicklungsperspektiven des Verarbeitenden Gewerbes von 31 westdeutschen Regionen im Globalisierungsprozess. Die amtliche Statistik liefert keine regionalen Direktinvestitionsdaten. Daher basiert die vorliegende Untersuchung auf Indikatoren der Unternehmensdatenbank INDAT, die Informationen über rund 6500 westdeutsche Industrieunternehmen für die Berichtsjahre 1986, 1990 und 1996 enthält. Die Studie zeichnet ein Bild der regionalen Verteilung des Direktinvestitionsengagements im westdeutschen Verarbeitenden Gewerbe. Die gegenwärtige Partizipation an den Glokalisierungsgewinnen und die mittelfristigen Entwicklungsperspektiven zeigen, dass die Regionen Hamburg, Darmstadt und Oberbayern zu den Gewinnern der Glokalisierung gehören. Um die langfristigen Entwicklungsperspektiven industrieller Kerne im Glokalisierungsprozess zu bewerten, untersuchen wir den Marktzugang zu den zukünftigen globalen Wachstumsregionen durch Direktinvestitionen. Hier zeigte sich, dass die Regionen Oberbayern, Stuttgart und Hamburg die besten langfristigen Entwicklungsperspektiven aufweisen. Zwischen 1986 und 1996 haben sich die Disparitäten zwischen den untersuchten Regionen hinsichtlich ihrer Integration in die internationale Arbeitsteilung durch Direktinvestitionsströme verringert, insbesondere zwischen peripheren Regionen.
Keywords: O18; F23; R11; 330; Regional Development; Agglomeration; Glocalisation; Manufacturing; Foreign Direct Investment; Direktinvestition; Verarbeitendes Gewerbe; Multinationales Unternehmen; Räumliche Verteilung; Agglomerationseffekt; Globalisierung; Regionales Wachstum; Regionale Entwicklung; Entwicklungspol; Deutschland; Globalisierung; Wirtschaftsprognose